Analisis Penerapan Promosi Sebagai Strategi dalam Meningkatkan Jumlah Nasabah Tabungan Emas Pegadaian (TEP) : (Studi Kasus PT. Pegadaian Unit Pelayanan Syariah Gobah Pekanbaru, Riau) - Sinta Yulia; Zulhelmi Zulhelmi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research is motivated by the decline in gold savings in the last four years due to: the value of gold which is currently getting higher, and Covid which occurred in mid-2020. Furthermore, people's needs are increasing and increasing so the ability to buy gold is low. To find out the analysis of the implementation of promotions as a strategy in increasing the number of pawnshop gold savings customers. This research uses a qualitative method using a descriptive approach. The types of data used are primary data sources and secondary data sources. The data collection techniques used by researchers are interviews, observation and documentation with customers and employees of PT.Pegadaian Syariah Gobah Pekanbaru Riau. Data processing techniques with data reduction, data editing, data description and drawing conclusions. Based on the research results, it can be concluded that the implementation of promotions is a strategy to increase the number of gold savings customers at PT.Pegadaian Syariah Gobah Pekanbaru Riau, is by using advertising promotions in introducing pawnshop gold savings products using social media and print media, promotions using online publications using websites is an effort to attract attention or news from the media or the general public for a product. can be widely known, Direct Promotion is carried out to attract potential customers by implementing socialization. Promotion Sales are carried out by providing special discounts or promo codes to prospective customers so that they are interested in pawnshop gold savings products at PT. PawnshopGobah Pekanbaru Riau Sharia Service Unit. By implementing promotional forms well, the goal can be achieved to increase the number of pawnshop gold savings customers and increase public understanding of pawnshop gold savings products and can help the community with economic problems.